1996
DOI: 10.3354/meps136213
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity of bacterioplankton communities assessed by flow cytometry and single carbon substrate utilization

Abstract: During the summer of 1994, bacterioplankton abundance and metabolism were examined in seawater from Bedford Basin, Nova Scotia. Canada. Two new methods were applied to independently assess metabolic activity: (1) flow cytometnc analysis of bimodal nucleic acid distributions in bacterioplankton stained with a novel fluorescent dye, and (2) utilization of single carbon substrates in Biolog GN Microplatcsl'' Both sets of results were compared to bacterial production estimates obtained using a standard technlque f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 10 publications
12
56
0
1
Order By: Relevance
“…Although little work has been performed to characterize the different DNA types of bacteria taxonomically and physiologically (Gasol & del Giorgio 2000), several studies revealed that high-DNA bacterial clusters exhibit a higher growth rate or cell-specific activity (Li et al 1995, Jellett et al 1996, Yamada et al 2000 and are more prone to protozoan grazing . The latter result is consistent with the reported size-and activity-selective grazing behavior of flagellates (Jürgens & Güde 1994, del Giorgio et al 1996, López-Amorós et al 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although little work has been performed to characterize the different DNA types of bacteria taxonomically and physiologically (Gasol & del Giorgio 2000), several studies revealed that high-DNA bacterial clusters exhibit a higher growth rate or cell-specific activity (Li et al 1995, Jellett et al 1996, Yamada et al 2000 and are more prone to protozoan grazing . The latter result is consistent with the reported size-and activity-selective grazing behavior of flagellates (Jürgens & Güde 1994, del Giorgio et al 1996, López-Amorós et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Flow sorting of Gulf of Mexico samples revealed that at least B-Ia (small cocci) and B-IV (rods, curved bacteria, large cocci) DNA types differ in morphology and species composition. Higher cell-specific uptake rates of 3 H-thymidine (Jellett et al 1996) and leucine ) of high-DNA bacteria might be seen in the context that bacteria with a 5-fold higher DNA content (Gasol & del Giorgio 2000) also need to incorporate 5 times as much thymidine for a single DNA replication. Still, the higher cell-specific growth rates of high-DNA cells in incubation experiments (Li et al 1995) leave grazer impact as an important, community-shaping process (Jürgens & Güde 1994) that deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial population was further divided into high DNA (HDNA) and low DNA (LDNA) categories according to variations in green fluorescence (Li et al 1995, Gasol et al 1999 (Fig. 2A), and the percentage of HDNA cells was then applied as a measure of the active proportion of cells within the bacterial community (Jellett et al 1996, Gasol et al 1999, Lebaron et al 2001.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al (1995) showed that their High DNA counts were better correlated to chlorophyll a than their Low DNA bacterial counts and that the fluorescence difference between the two groups was positively related to chlorophyll. In a follow-up paper, Jellett et al (1996) compared the %HDNA (which they called "Active cell index") to tritiated substrate uptake rates and found patterns that were similar but not entirely coherent. They also determined that the High DNA cells had on average 5 times more DNA per cell than did the Low DNA cells.…”
Section: Dna Content Of Individual Bacteriamentioning
confidence: 99%